1998
DOI: 10.1016/s0735-1097(97)00437-3
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Inhibition Impairs Blood Flow During Exercise in Hearts With a Collateral-Dependent Myocardial Region

Abstract: NO contributes to the maintenance of coronary collateral blood flow during exercise. In contrast to the normal heart, endogenous NO production also maintains blood flow in remote myocardial regions during exercise. These results suggest that control of blood flow during exercise in normal myocardium is altered by the presence of an occluded coronary artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…20,29 Furthermore, NO could positively affect latent collaterals or collateral blood flow by eliciting vasodilatation or inhibiting platelet aggregation in the vascular bed distal to the target lesion. 22,30 These mechanisms 15,16,[19][20][21][22][28][29][30] can explain why NTP was more effective than NTG in improving the final angiographic results. Second, recent studies have demonstrated that HBTF 4 and lipid pool-like content 31 in large IRAs are predictors of slow-flow or no-reflow, because distal macro-and microembolism of thrombi and plaque material frequently occurs in these vessels during balloon dilatation or stenting, which, in turn, induces severe microvascular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…20,29 Furthermore, NO could positively affect latent collaterals or collateral blood flow by eliciting vasodilatation or inhibiting platelet aggregation in the vascular bed distal to the target lesion. 22,30 These mechanisms 15,16,[19][20][21][22][28][29][30] can explain why NTP was more effective than NTG in improving the final angiographic results. Second, recent studies have demonstrated that HBTF 4 and lipid pool-like content 31 in large IRAs are predictors of slow-flow or no-reflow, because distal macro-and microembolism of thrombi and plaque material frequently occurs in these vessels during balloon dilatation or stenting, which, in turn, induces severe microvascular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a contribution from impaired microvascular dilation, especially in cases of steal, is suggested by results of experimental studies in laboratory animals. [17][18][19][20] Maximal blood flow and conductance in collateral supply myocardium also were abnormal even in segments with normal contraction at rest (Tables 4 and 5). Because supply vessels had either no or only mild stenosis, reduced maximal blood flow may reflect a contribution from microvascular dysfunction in collateral supply myocardium.…”
Section: Discussion Principal Findingsmentioning
confidence: 98%
“…Because supply vessels had either no or only mild stenosis, reduced maximal blood flow may reflect a contribution from microvascular dysfunction in collateral supply myocardium. [17][18][19] It is possible, however, that abnormal flow reserve in collateral supply myocardium reflects the fact that a single conduit vessel must serve the needs of Ն2 vascular beds. 12,13 Under such conditions and in the presence of either diffuse atherosclerosis or even mild focal stenosis, impedance to flow in the conduit supply artery may be increased substantially and could contribute importantly to reduced maximal blood flow and conductance in the collateral supply bed.…”
Section: Discussion Principal Findingsmentioning
confidence: 99%
“…After occlusions had been performed for 3 wk, the artery was permanently occluded. We previously observed that this degree of collateralization is sufficient to allow permanent coronary occlusion without producing infarct (31). Studies were performed after permanent occlusion had been in place for 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…VEGF has been shown to upregulate eNOS expression in vascular endothelial cells but can also induce iNOS expression (4,26,30). Vascular NO effects are increased in collateralized hearts, since nonselective inhibition of NO production with N G -nitro-L-arginine (LNA) significantly decreased blood flow in collateral-dependent myocardium but did not decrease blood flow in normal hearts (22,31). Whether this increased NO effect in collateralized hearts results from constitutive NOS or from inducible NO synthase (iNOS) is unknown.…”
mentioning
confidence: 99%